Taylor Glacier Tunnel: Measurements of the composition, deformation and strength of basal ice made in a tunnel in Taylor Glacier, Antarctica ... - Fitzsimons, Sean (Zenodo, 2023)
Data set from Taylor Glacier tunnel Photographs of tunnel excavation Video of tunnel excavation ...